Pengaruh Media Sosial Youtube Terhadap Peningkatan Karakter Siswa Pencak Silat - Hammy Hammy; Rasyidah Jalil; Imam Pribadi; Irsan Kahar Kahar; Rachmat Hidayat; Ahmad Syarif Burhan (Jurnal Porkes, 2025)
The low participation and difficulty in mastering movements among pencak silat students at MAN Palopo are thought to have an impact on their character development. This study aims to analyze the influence of YouTube social media on improving the character of pencak silat students. The method used is quantitative with a correlation approach. The population consisted of 100 students, with a sample of 20 people selected purposively based on the criteria of using YouTube to learn pencak silat for at least one hour per week. Data collection techniques used questionnaires and observations, which were then analyzed using Pearson's correlation test, regression, T-test, and F-test using SPSS. The results showed a very strong and significant relationship between YouTube usage and student character (r = 0.712; p < 0.05). Regression analysis proved that YouTube had a positive and significant effect on character building (β = 0.610; p < 0.05), which was reinforced by significant T-test and F-test results. The conclusion of this study is that the use of YouTube social media containing educational content on pencak silat has been proven to significantly improve students' positive character traits, such as discipline, responsibility, and respect.